Incidental Finding of Tl-201 Accumulation in an Empyema - Demircali A.E.; Basoglu T.; Bernay I.; Sahin M. (My University, 1996)
A 47-year-old man with Behcet disease was hospitalized because of abdominal pain. Abdominal ultrasonography revealed a 3 cm x 3 cm hepatic mass and chest x-ray showed an empyema of the right lung. The patient was placed in a protocol for Tl-201 uptake in hepatic tumors. Surprisingly, Tl-201 accumulation was seen in the inferior lobe of the right lung within the empyema.